Comparative analysis of antipsychotic drug consumption for inpatient schizophrenia treatment: a retrospective study with 5-year follow-up - L. B. Vaskova; M. V. Tiapkina; E. V. Mikhaylenko (IRBIS LLC, 2020)
Aim. The study was aimed to perform a comparative retrospective pharmacoepidemiological analysis of antipsychotic drugs (APD) used for inpatient treatment for schizophrenia.Materials and methods. This retrospective pharmacoepidemiological study included 1077 medical records of patients diagnosed with schizophrenia according to ICD-10 (F20.0-F20.8) selected for the analysis on the base of a psychiatric inpatient hospital in Moscow during 2013-2017. The study design included socio-demographic data (sex, age, education, disability, social status) and clinical-economic data (diagnoses, duration of hospitalization), information on the prescription frequency of drugs and dose regimens were analyzed. The consumption volume of APD was estimated using the WHO ATS/DDD methodology.Results and discussion. It was found that women prevailed (55-71%) with the mean age ranging from 42.8±14.1 to 47.4±14.7 (±SD - standard deviation). In the studied sampling, paranoid schizophrenia dominated (≥70%). Over the analyzed 5-year period, the consumption volume of APDs was characterized by alternating declines and rises (from 154.49 to 208.09 NDDD/100 bed-days). The consumption of atypical APDs decreased by 7% and typical APDs increased by 25% compared to the base year (2013), respectively. The most significant changes in the consumption were identified for APDs of prolonged action (a decrease by 67% compared to 2013). Haloperidol and clozapine (oral forms), which are included in the DU90% segment, remained the leaders in terms of prescription frequency and consumption volume (49.04 and 45.26 NDDD/100 bed days in 2017, respectively). Moreover, trihexiphenydil (used to correct adverse reactions) also had a high frequency of administration and consumption.Conclusion. It was found that 1/2 of all prescriptions were antipsychotic drugs used to treat schizophrenia. The total consumption volume of APDs in 2017 decreased by 9.2% compared to 2013. A high consumption volume is typical for drugs from the subgroup of typical APDs, but atypical APDs prevailed in terms of prescription frequency, which may indicate the prescription of typical APDs in doses exceeding the defined daily dose.